Sustainability in the European Union: Analyzing the discourse of the European Green Deal - Eva Eckert; Oleksandra Kovalevska (Journal of Risk and Financial Management, 2021)
In the European Union, the concern for sustainability has been legitimized by its politically and ecologically motivated discourse disseminated through recent policies of the European Commission and the local as well as international media. In the article, we question the very meaning of sustainability and examine the European Green Deal, the major political document issued by the EC in 2019. The main question pursued in the study is whether expectations verbalized in the Green Deal's plans, programs, strategies, and developments hold up to the scrutiny of critical discourse analysis. We compare the Green Deal's treatment of sustainability to how sustainability is presented in environmental and social science scholarship and point out that research, on the one hand, and the politically motivated discourse, on the other, do not correlate and often actually contradict each other. We conclude that sustainability discourse and its keywords, lexicon, and phraseology have become a channel through which political institutions in the EU such as the European Commission sideline crucial environmental issues and endorse their own presence. The Green Deal discourse shapes political and institutional power of the Commission and the EU.
Keywords: 330; economic growth; sustainability; critical discourse analysis; plastic waste; the European Green Deal